Incidence of Dementia in Patients With Open-angle Glaucoma: A Population-based Study. Issue 3 (29th March 2021) - Belamkar, Aditya V.; Mansukhani, Sasha A.; Savica, Rodolfo; Spiegel, Matthew R.; Hodge, David O.; Sit, Arthur J.
Abstract : Precis: In this population-based study of 509 open-angle glaucoma (OAG) patients over a 36-year period, we identified a decreased rate of developing dementia compared with the rate in the general population. Purpose: The aim was to determine the incidence of dementia and Alzheimer disease (AD) among patients with OAG. Patients and Methods: Retrospective, population-based cohort study. All residents of Olmsted County, Minnesota (≥40 y) who were diagnosed with OAG between January 1, 1965 and December 31, 2000, were eligible for inclusion in this study. A total of 509 patients were included over the 36-year period. The cumulative probability of developing dementia was calculated and compared with the population risk of dementia. Results: Of the 509 patients included, 300 (58.9%) were female, the median age was 67.5 years, and 278 patients (54.6%) had primary OAG. Other subgroups were pseudoexfoliation in 15.1%, treated ocular hypertension in 14.1%, normal tension glaucoma in 10.6%, and pigmentary glaucoma in 5.5% of the patients. Respectively, 118 (23.0%) and 99 (19.4%) patients developed dementia and AD. The 10-year cumulative probability of developing dementia and AD was 12.0% and 9.9%, with a 95% confidence interval of 9.3%-15.3% and 7.5%-13%, respectively. The observed 10-year incidence of dementia and AD were significantly lower than the expected population incidence (19.0% and 19.0%; P <0.001). Older age at diagnosis of glaucoma was a strong predictor for the development of dementia by multivariate analysis (hazard ratio: 3.31, 95% confidence interval: 2.61-4.20, P <0.001). Conclusion: The risk of developing dementia or AD was decreased in OAG patients compared with the general population. OAG with onset at a later age may present as a different etiopathogenetic entity compared with onset at a younger age, and represent the optic nerve findings of generalized neurodegenerative processes.